Pressure Injury Prevention: Patient Education for Spinal cord Injury Patients- The I mportance of Teaching Nurses to Teach - Sheppard, Thomas (Jour Med Resh and Health Sci, 2022)
Abstract Patient education is an essential component of preventing the occur-rence of pressure injuries. Patients that have suffered a spinal cord injury are at severe risk of developing pressure injuries throughout their lifetimes. There are many factors that nurses need to be aware of to provide effective patient education and promote positive patient outcomes. While all nurses can provide basic information, many of them are not proficient teachers. To enhance patient education, this article review will identify various important factors that affect the ability of spinal cord injury patients to learn and the nurse’s ability to provide effective patient education about risk factors for pressure injury development preventive measures to reduce the risk of developing pressure injuries.